Williams Syndrome presenting with Supra valvular Aortic Stenosis: A Case Report - Islam, SM Shaheedul; Cader, F Aaysha; Haq, M Maksumul; Md Rokonujjaman, -; Nasrin, Sahela (Ibrahim Cardiac Medical Journal, 2015)
Williams Syndrome is described in children presenting with Supra-valvular Aortic Stenosis (SVAS) and typical dysmorphic 'Elfin facies' with characteristic neurocognitive profile. SVAS, a congenital narrowing of the ascending aorta, occurs sporadically but can also occur as a component of Williams Syndrome, with which it shares similar genetic microdeletion of the elastin gene on chromosome 7qll.23, responsible for the vasculopathy as well as certain morphological features of the syndrome. We report the case of a 5 year old girl, who presented with chest pain and a heart murmur, along with typical 'Elfinfacies', whose investigation led to the diagnosis of SVAS presenting with Williams Syndrome. Ibrahim Cardiac Med J 2014; 4(1): 42-47